2018
DOI: 10.3390/brainsci8050076
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Manipulation Increases Maximal Bite Force in Healthy Individuals

Abstract: Recent research has shown that chiropractic spinal manipulation can alter central sensorimotor integration and motor cortical drive to human voluntary muscles of the upper and lower limb. The aim of this paper was to explore whether spinal manipulation could also influence maximal bite force. Twenty-eight people were divided into two groups of 14, one that received chiropractic care and one that received sham chiropractic care. All subjects were naive to chiropractic. Maximum bite force was assessed pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…This finding was similar to a previous study, which showed an increase in quadriceps strength following spinal manipulation in participants with anterior knee pain [ 63 ]. An increase in muscle strength following spinal manipulation has also been noted in other muscle groups, such as the upper limb, trunk, and jaw muscles [ 64 , 65 , 66 , 67 ]. Interestingly, a significant increase in bite force, which was retained up to one week after the spinal manipulation session, was noted in people with a history of mild recurring spinal dysfunction, indicating maintenance of the beneficial effects of spinal manipulation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to a previous study, which showed an increase in quadriceps strength following spinal manipulation in participants with anterior knee pain [ 63 ]. An increase in muscle strength following spinal manipulation has also been noted in other muscle groups, such as the upper limb, trunk, and jaw muscles [ 64 , 65 , 66 , 67 ]. Interestingly, a significant increase in bite force, which was retained up to one week after the spinal manipulation session, was noted in people with a history of mild recurring spinal dysfunction, indicating maintenance of the beneficial effects of spinal manipulation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in muscle strength following spinal manipulation has also been noted in other muscle groups, such as the upper limb, trunk, and jaw muscles [ 64 , 65 , 66 , 67 ]. Interestingly, a significant increase in bite force, which was retained up to one week after the spinal manipulation session, was noted in people with a history of mild recurring spinal dysfunction, indicating maintenance of the beneficial effects of spinal manipulation [ 64 ]. Although most of these studies have been conducted in relatively healthy populations, a recent study was conducted in a group that had lost their ability to cortically activate their muscles, i.e., chronic stroke patients with ongoing plantar flexor muscle weakness [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to keep in mind that previous work has shown that some neuroplastic effects of chiropractic spinal manipulation can, in some instances, remain for at least a week [74]. This may have affected the current study because it could have reduced or nullified the changes in this study, where both interventions were performed within a week.…”
Section: Study Considerationsmentioning
confidence: 95%
“…The spine is the biomechanical and neurological connection between the brain and limbs and there is evidence that changes in afferent signals from the spine can alter central neural processing [ 13 ], which can impact motor control of the limbs [ 11 , 12 , 14 , 19 , 20 , 21 ]. Numerous studies demonstrated that chiropractic spinal adjustments can alter paraspinal mechanical afferent input, as well as central somatosensory processing, sensorimotor integration, and motor control [ 13 ], not only relating to spinal motor control, but also of the limbs, pelvic floor muscles, and even jaw muscles [ 11 , 12 , 14 , 19 , 20 , 21 , 22 , 23 ]. Sensorimotor integration is the ability of the CNS to produce appropriate motor output by integrating sensory inputs from the body and environment [ 13 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%